Coagulation behavior of silica, hematite and nickel oxide in relation to natural nickel laterite ore in aqueous environment - Espiritu, Eileen Ross L. (2012)
The study aims to investigate the coagulation behavior of fine silica, hematite and nickel oxide minerals in aqueous environment of various types of electrolyte (KCl, BaCl2, and LaCl3) as a function of pH. The coagulation behaviors of these minerals, either as one, two, or three component systems are observed at pH 3 to 11 by measuring the changes in the transmittance of the resulting dispersions at different time intervals. The observed coagulation responses are related to the possible behavior of nickel laterite ore in natural environment. Zeta potential values of these minerals are initially measured using electrophoretic method as a function of electrolyte type at various pH conditions. The isoelectric points (i.e.p.) of silica, hematite, and nickel oxide minerals are determined to be around pH 2, 6.5, and 8, respectively. Hamaker constants of each mineral in aqueous medium are calculated by the determination of the critical coagulation concentration (CCC) which is found to decrease as the valence ratios of the supporting electrolyte increases. Moreover, coagulation rates of all the systems are found to increase with increasing valence ratio. The result showed that the condition where the three-component system exhibits rapid coagulation in aqueous suspension is at pH 3-7 with LaCl3 as the supporting electrolyte. This behavior is also shown by the nickel laterite ore which implies that the coagulation behavior of the ore can be estimated by studying its components. The results of coagulation behavior in this study are consistent with the Schulze-Hardy rule and the classical DLVO (Derjaguin, Landau, Vervey, and Overbeek) theory.